2017
DOI: 10.17221/268/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in the food packaging market - intelligent packaging - a review

Abstract: Barska A., Wyrwa J. (2017): Innovations in the food packaging market -intelligent packaging -a review. Czech J. Food Sci., 35: 1-6.The manufacturers have to provide modern and safe packaging due to the growing consumer interest in the consumption of fresh products with extended shelf-life and controlled quality. It is a challenge to the food packaging industry and it also acts as a driving force for the development of new and improved concepts of packaging technology. It is in order to meet these needs that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Furthermore, it was observed that all substances steadily and constantly change their color upon the carried out aging processes ( Figure 4 b and Figure 6 ). Thus, the applied natural substances, apart from their application as natural antioxidants, might be very promising regarding the bio-based aging indicators for, e.g., food packaging [ 48 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was observed that all substances steadily and constantly change their color upon the carried out aging processes ( Figure 4 b and Figure 6 ). Thus, the applied natural substances, apart from their application as natural antioxidants, might be very promising regarding the bio-based aging indicators for, e.g., food packaging [ 48 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of smart packaging systems has contributed towards a significant change in the existing perception of packaging, since they transform the traditional communication functions of packaging into intelligent communications [22], and interact with the consumer in terms of their ability to detect changes in the environment of the products [41].…”
Section: Methodsmentioning
confidence: 99%
“…Field research has been carried out on packaging characteristics and technologies [21]. This is evidenced by the number of patents and patent applications granted in recent years [22].…”
Section: Introductionmentioning
confidence: 99%
“…This could be partially caused by differences in individual cultures or by lack of understanding of their advantages. Only a few products packed this way are offered in the market compared to the number of options mentioned in the literature, but it is likely these disproportions will be solved and smart packaging soon becomes generally available [27]. Over the last 20 years an important improvement in active packaging systems has been observed.…”
Section: Smart Packagingmentioning
confidence: 99%
“…Benefits of smart packaging are clear. However, there are still questions that must be solved before packaging of this type spreads widely [27]. The issue of smart packaging is very attractive from the point of view of consumers and it makes them curious.…”
Section: Table 1 the Smart Packaging Perception In Different Age Catementioning
confidence: 99%